Making a living : the livelihoods of the rural poor in Bangladesh - Khan, Iqbal Alam.; Seeley, J. A.; Livelihoods of the Extreme Poor Study (Project : Bangladesh) (Dhaka : University Press, 2005)
Contributed articles prepared under the Livelihoods of the Extreme Poor Study Project, Bangladesh.
Includes bibliographical references (p. 221-233) and index.
BIED
Keywords: Rural poor -- Bangladesh -- Economic conditions; Bangladesh -- Rural conditions